Acute complications in children with sickle cell disease: Prevention and management. Issue 1 (7th March 2022) - Beck, Carolyn E; Trottier, Evelyne D; Kirby-Allen, Melanie; Pastore, Yves
Abstract: Sickle cell disease (SCD) is a chronic, multi-system disease that requires comprehensive care. The sickling of red blood cells leads to hemolysis and vascular occlusion. Complications include hemolytic anemia, pain syndromes, and organ damage. Patterns of immigration and an increase in newborn screening mean that paediatric health care providers across Canada, in small and large centres alike, need to be knowledgeable about SCD. This statement focuses on principles of prevention, advocacy, and the rapid treatment of common acute complications. Guidance includes the current status of newborn screening, recommendations for immunizations and antibiotic prophylaxis, and an introduction to hydroxyurea, a medication that reduces both morbidity and mortality in children with SCD. Case vignettes demonstrate principles of care for common acute complications of SCD: vaso-occlusive episodes (VOE), acute chest syndrome (ACS), fever, splenic sequestration, aplastic crises, and stroke. Finally, principles of blood transfusion are highlighted, along with indications for both straight and exchange blood transfusions.